How to Link Brain and Experience? Spatiotemporal Psychopathology of the Lived Body - Northoff, Georg; Stanghellini, Giovanni (Frontiers in Human Neuroscience, 2016)
The focus of the present paper is on sketching a psychopathology of the body in schizophrenia. Our hypothesis is that the psychopathological alterations of the lived body are closely related to spatiotemporal alterations in the brain’s resting state. Hence our plea for a spatiotemporal psychopathology of embodiment. We will shed some light on the resting state itself, its spatiotemporal structure and self-specific organisation and then address the resting state’s spatial and temporal abnormalities in schizophrenia and how they account for the abnormal experience of body, time, and space in this psychopathological condition. Finally, we sketch the implications of such spatiotemporal psychopathology of embodiment that concerns the spatialization and temporalization and self-specification of the lived body and its intero-, proprio- and extero-ceptive input by the resting state’s spatiotemporal structure and self-specific organisation.